Evaluating the effects of climate change on Arctic char : including impacts of brown trout competition - Carlström, Ola (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2023)
Climate change is predicted to increase the average global temperature with 1.5 °C between 2030 and 2052. The areas that are most vulnerable for climate change are the arctic regions. Arctic char (Salvelinus alpinus) is a cold-water salmonid species with the most northern distribution of all freshwater fish species. The distribution area of Arctic char in Sweden is predicted to decrease with 73 % by 2100, both as a result of warmer climate and changed species interactions. Here, I have studied how climate change will affect the habitat- and food choice as well as the growth of Arctic char, both in waters where brown trout (Salmo trutta) are absent (Abiskojaure), and in waters where they are present (Stor-Björsjön). By analysing available catch data from both lakes, habitat selection of Arctic char and brown trout could be studied. Food choice was studied by examining stomach content, and growth by measuring annual growth rings on otoliths. My results show that the habitat selection of Arctic char in Abiskojaure was only dependent on the size of the fish, where fish in the small and large size ranges (< 101 mm, 301 – 400 mm and > 400 mm) were found in shallower water compared to fish in the intermediate size ranges (101 – 200 mm and 201 – 300 mm). In Stor-Björsjön the habitat selection for Arctic char was dependent on both size of fish and surface temperature. In Stor-Björsjön, Arctic char in the small and large size ranges (< 101 mm and > 300 mm) were found at a wider range of depths compared to Arctic char in the intermediate size ranges (101 – 200 mm and 201 – 300 mm), which were found in a more limited depth span. The Arctic char tended to stay deeper as surface temperatures increased, and where brown trout was present. Arctic char’s diet in Abiskojaure mainly consisted of crustaceans, but in Stor-Björsjön, pelagic zooplankton were the main food source. Differences in annual growth could be seen between younger and older Arctic char. In Abiskojaure warm or cold years did not affect the annual ...